Pengaruh Penggunaan Media Boneka Tangan Terhadap Keterampilan Berbicara Siswa Kelas I SDN 17 Jebus - Saputri, Endah; Asyraf Suryadin; Silvio Juliana Nabela (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACTThis study was motivated by students’ difficulties in verbally expressing ideas an opinions. It was indicated by 15 students who spoke with traditional language and often chose inappropriate words when conveying their intentions in indonesian language. This study aimed to determine the effect of using hand puppet media on speaking skills of Grade I students at SD Negeri 17 Jebus. This study used a pre-experimental design with a one-group pretest-posttest model, measuring the same group before and after the intervention. The subjects consisted of 29 Grade I students of SD Negeri 17 Jebus. The data were collected using a test as the main instruement. Data analysis involved a normality test and hypothesis testing using a paired sample t-test. The results demonstrated a significant improvement in the students’ average scores, increasing from 51.2 (pretest) to 79.4 (posttest), with a significance value of 0.001 (<0.05). The normality test confirmed that both the pretest (0.060 > 0.05) and posttest (0.062 > 0.05) data followed a normal distribution. The hypothesis test produced a significance value 0.001 and a (9.964) that exceeded the value (2.048), leading to the rejection of the null hypothesis . These findings confirm that using hand puppet media significantly improves the speaking skills of Grade I students at SD Negeri 17 Jebus.